Animals living in polluted environments are a potential source of anti-tumour 2 molecule(s) - Jeyamogan, Shareni; Khan, Naveed Ahmed *; Siddiqui, Ruqaiyyah Bano * (American Chemical Society, 2017)
Despite advances in in therapeutic interventions and supportive care, the morbidity and mortality associated with cancer has remained significant. Thus there is a need for newer and more powerful anti-tumour agents. The search for new anti-tumour compounds originating from natural resources is a promising research area. Animals living in polluted environments are a potent source of anti-tumour agents. Under polluted milieus, species such as crocodiles, feed on rotten meat, are exposed to heavy metals, endure high levels of radiation, are among the very few species to survive the catastrophic Cretaceous-Tertiary extinction event with a prolonged lifespan. Thus it is reasonable to speculate that animals such as crocodiles have developed mechanisms to defend themselves against cancer. The discovery of antitumor activity in animals such as crocodiles, whales, sharks, etc will stimulate research in finding therapeutic molecules from unusual sources, and has potential for the development of novel antitumor compound(s) that may also overcome current drug resistance. Nevertheless, intensive research in the next few years will be required to realize these expectations.